Dental care for children with Down Syndrome: Literature review (Research, Society and Development, 2021)
Down syndrome (DS) is an autosomal chromosomal disorder caused by trisomy 21. It is the most frequent congenital mental anomaly and encompasses numerous mental and behavioral changes, including physical and oral changes, which require attention from dental surgeons. The dental treatment of these patients consists in eliminating or controlling the difficulties they have, adapting the conduct and making an early approach as the best option. The dental surgeon, when aware of all these complications and intra and extra oral characteristics, will be able to perform a better dental management. The present work is a qualitative narrative review, carried out in the Virtual Health Library (VHL), Pubmed and Scielo databases, using the keywords: “Down syndrome”, “dentistry” and “behavioral management”, as well as their English counterparts. The study aims to characterize the behavioral management techniques used in pediatric dental care for children with Down syndrome and to identify the main points about the conduct of the dental surgeon during dental care for these patients. With this study, it was concluded that there is still considerable controversy among authors regarding the high or low rate of caries lesions in these patients. It is also understood the importance of family monitoring throughout the dental treatment and the need for the dental surgeon to be well prepared and know how to deal with all the characteristics and particularities of each child.